Superstructure Planning of 21 Floor Swasana Building Anami Tower B Klapa Village Project - Ambrosius Yosefus Sirie (Journal of Global Engineering Research and Science, 2022)
The structural planning of building construction is needed to get the most effective and efficient dimensions and configuration of the structure. Planning a building structure located in an earthquake-prone area must be planned according to standards, is strong, and is earthquake-safe. The Planning of the Superstructure of the Swasana Building 21 Floors Anami Tower B the Klapa Village Project refers to the Procedures for Planning for Concrete Structures and Buildings of SNI 2847-2019, and the Standards for Planning Earthquake Resistance for Building Structures of SNI 1726-2019. Planning of the Superstructure of the 21-Story Swasana Building Tower B of the Klapa Village project uses Etabs V.17 software which includes the planning of beams, columns, and floor slabs. Loads that are reviewed for the design of structural elements are dead load, live load, and earthquake load.